Promoting Handwashing Behavior in Peru : The Effect of Large-Scale Mass-Media and Community Level Interventions - Galiani, Sebastian; Gertler, Paul; Orsola-Vidal, Alexandra (World Bank, Washington, DC, 2014)
This paper analyzes a randomized experiment that uses novel strategies to promote handwashing with soap at critical times in Peru. It evaluates a large-scale intervention that includes a mass media provincial campaign and a district-level community component. The analysis finds that the mass media intervention alone had no significant effect on exposure to the handwashing promotion campaign messages, and therefore no effect on handwashing knowledge or handwashing behavior. In contrast, the community-level intervention, a more comprehensive intervention that included several community and school activities in addition to the communications campaign, was successful in reaching the target audience with handwashing promotion messages and in improving the knowledge of the treated population on appropriate handwashing behavior. Those improvements translated into higher self-reported and observed handwashing with soap at critical junctures. However, no significant improvements in the health of children under the age of five were observed. The results are consistent with earlier literature, which indicates that substantively changing behavior to improve health is a complex task requiring intensive and more personalized interventions.